GLIMPSE STUDY: IMPACT OF TRIPLE THERAPY ON LUNG FUNCTION, HEALTH STATUS, AND MORTALITY RISK IN PATIENTS WITH ADVANCED CHRONIC OBSTRUCTIVE PULMONARY DISEASE - HEBA, SALVA FATIMA; ALI, SYED AAMIR; ALEEMUDDIN NAVEED, MOHAMMED; MEHRIN, SALWA; GULNAAZ, MAARIA; FATIMA, NAUSHEEN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The objectives of the study were to estimate the relative impact of triple therapy on lung function, health status, and mortality risk compared with combination inhaled corticosteroid (ICS)/long-acting β-agonist (LABA) therapy in symptomatic chronic obstructive pulmonary disease (COPD) patients with frequent exacerbations in an Indian clinical population. Methodology: The GLIMPSE (Lung Function, Health Status, and Mortality Risk Assessment in COPD using Triple Therapy) was as a prospective, parallel design, single-center observational study comparing 24 weeks of triple therapy (twice-daily combination of budesonide [BUD]-formoterol [FOR] [100/6 μg] and once-daily tiotropium [TIO] [9 μg]) with ICS/LABA (twice daily BUD-FOR [100/6 μg]). The primary outcome was the mean change in forced expiratory volume in the 1st s (FEV1%) predicted and COPD assessment test total score from baseline at week 24. Secondary outcomes were variation in dyspnea grade and BODE total score from baseline. Results: At week 24 in triple therapy (n=70) and ICS/LABA therapy (n=70), mean difference from baseline in FEV1% predicted were 5.40 (95% confidence interval [CI]: 1.29–9.50) and 1.90 (95% CI: –1.87–5.68) respectively, and mean difference in CAT total score from baseline was –5.10 units (95% CI: –3.49–−6.71) and –1.80 units (95% CI: –0.052–−3.548), respectively. In addition, there was a statistically significant reduction in dyspnea grading and BODE score with comparable adverse events in both groups. Conclusion: Overall, the results favored triple therapy over dual therapy in advanced symptomatic COPD patients.